Characterizing Current Attitudes and Practices for Human Subject Safety in Studies Involving Pupil Dilation. (February 2021) - Szpernal, Jacob; Carroll, Joseph; Spellecy, Ryan; Bachman Groth, Jane A.
Standards in pupil dilation practices regarding the safety of human subjects are not present in vision research despite the potential for significant adverse effects. We developed two surveys to examine current practices around pupil dilation among vision researchers and individuals associated with oversight of human subjects research. While both groups note an absence of adverse events associated with pupil dilation, vision researcher practices differed with informed consent use and measures taken to minimize complications. For Institutional Review Boards, general risk assumption associated with dilation was not unanimous and there was a lack of specific guidance available to researchers for minimizing risk. These results uncover the need for standardized practices regarding pupil dilation in human subjects research.